Respuesta :
Given two endpoints: [tex](x_1,\ y_1)[/tex] and [tex](x_2,\ y_2)[/tex], the midpoint of the two endpoints [tex](x_m,\ y_m)[/tex] is given by
[tex](x_m,\ y_m)=\left( \frac{x_1+x_2}{2} ,\ \frac{y_1+y_2}{2}\right) [/tex]
Thus, given the midpoint L(-1, 8) and one endpoint J(4, -15). The second endpont is given by
[tex](-1,\ 8)=\left( \frac{x_1+4}{2} ,\ \frac{y_1+(-15)}{2}\right)[/tex]
i.e.
[tex]\frac{x_1+4}{2} =-1 \\ \\ x_1+4=-2 \\ \\ x_1=-2-4=-6[/tex]
and
[tex]\frac{y_1+(-15)}{2}=8 \\ \\ y_1-15=16 \\ \\ y_1=16+15=31[/tex]
[tex](x_m,\ y_m)=\left( \frac{x_1+x_2}{2} ,\ \frac{y_1+y_2}{2}\right) [/tex]
Thus, given the midpoint L(-1, 8) and one endpoint J(4, -15). The second endpont is given by
[tex](-1,\ 8)=\left( \frac{x_1+4}{2} ,\ \frac{y_1+(-15)}{2}\right)[/tex]
i.e.
[tex]\frac{x_1+4}{2} =-1 \\ \\ x_1+4=-2 \\ \\ x_1=-2-4=-6[/tex]
and
[tex]\frac{y_1+(-15)}{2}=8 \\ \\ y_1-15=16 \\ \\ y_1=16+15=31[/tex]
Answer:
Its A and C!!
Step-by-step explanation:
took the quiz